Answer

Verified

434.1k+ views

Hint: In this question, the equation of circle is given. To find the y-intercept made by a circle we will first convert the given circle equation into the standard circle equation and then use the formula for y-intercept to the value of y-intercept.

Complete step-by-step answer:

In the question, it is given that:

Equation of circle is $5{{\text{x}}^2} + 5{{\text{y}}^2} - 2{\text{x + 6y - 8 = 0}}$ .

We have to find the y-intercept made by the given circle.

We know that the standard equation of circle is given by:

${{\text{x}}^2} + {{\text{y}}^2} + 2{\text{gx + 2fy + c = 0}}$. (1)

Y-intercept of this circle is given by $2\sqrt {{{\text{f}}^2} - c} $ .

But the equation of the circle given is not in the standard form. So we will first convert this equation in standard form.

$

\Rightarrow 5{{\text{x}}^2} + 5{{\text{y}}^2} - 2{\text{x + 6y - 8 = 0}} \\

$

On dividing the above equation by 5, we get,

$

\Rightarrow {{\text{x}}^2} + {{\text{y}}^2} - \dfrac{2}{5}{\text{x + }}\dfrac{6}{5}{\text{y - }}\dfrac{8}{5}{\text{ = 0}} \\

$

So the above equation is the standard equation of a circle.

On comparing the above equation with equation 1, we get:

$

2{\text{g = - }}\dfrac{2}{5} \\

\Rightarrow {\text{g = - }}\dfrac{1}{5}. \\

{\text{And}} \\

{\text{2f = }}\dfrac{6}{5}. \\

\Rightarrow {\text{f = }}\dfrac{3}{5},{\text{ and c = - }}\dfrac{8}{5}. \\

$

Y-intercept made by circle =$2\sqrt {{{\text{f}}^2} - c} $.

Putting the value of ‘f’ and ‘c’ in the above formula, we get:

Y-intercept made by circle = $2\sqrt {{{\text{f}}^2} - c} = 2\sqrt {{{\left( {\dfrac{3}{5}} \right)}^2} - \left( { - \dfrac{8}{5}} \right)} = 2\sqrt {\dfrac{9}{{25}} + \dfrac{8}{5}} = 2\sqrt {\dfrac{{49}}{{25}}} = 2 \times \dfrac{7}{5} = \dfrac{{14}}{5}.$

Note: In this type of question, the first important thing is to clearly see the question whether it is asking y-intercept or x-intercept. Then convert the given equation into a standard form of equation. You should remember the formula for finding y-intercept. Compare the transformed given equation with the standard equation to get the value of parameters required for computing the y-intercept.

Complete step-by-step answer:

In the question, it is given that:

Equation of circle is $5{{\text{x}}^2} + 5{{\text{y}}^2} - 2{\text{x + 6y - 8 = 0}}$ .

We have to find the y-intercept made by the given circle.

We know that the standard equation of circle is given by:

${{\text{x}}^2} + {{\text{y}}^2} + 2{\text{gx + 2fy + c = 0}}$. (1)

Y-intercept of this circle is given by $2\sqrt {{{\text{f}}^2} - c} $ .

But the equation of the circle given is not in the standard form. So we will first convert this equation in standard form.

$

\Rightarrow 5{{\text{x}}^2} + 5{{\text{y}}^2} - 2{\text{x + 6y - 8 = 0}} \\

$

On dividing the above equation by 5, we get,

$

\Rightarrow {{\text{x}}^2} + {{\text{y}}^2} - \dfrac{2}{5}{\text{x + }}\dfrac{6}{5}{\text{y - }}\dfrac{8}{5}{\text{ = 0}} \\

$

So the above equation is the standard equation of a circle.

On comparing the above equation with equation 1, we get:

$

2{\text{g = - }}\dfrac{2}{5} \\

\Rightarrow {\text{g = - }}\dfrac{1}{5}. \\

{\text{And}} \\

{\text{2f = }}\dfrac{6}{5}. \\

\Rightarrow {\text{f = }}\dfrac{3}{5},{\text{ and c = - }}\dfrac{8}{5}. \\

$

Y-intercept made by circle =$2\sqrt {{{\text{f}}^2} - c} $.

Putting the value of ‘f’ and ‘c’ in the above formula, we get:

Y-intercept made by circle = $2\sqrt {{{\text{f}}^2} - c} = 2\sqrt {{{\left( {\dfrac{3}{5}} \right)}^2} - \left( { - \dfrac{8}{5}} \right)} = 2\sqrt {\dfrac{9}{{25}} + \dfrac{8}{5}} = 2\sqrt {\dfrac{{49}}{{25}}} = 2 \times \dfrac{7}{5} = \dfrac{{14}}{5}.$

Note: In this type of question, the first important thing is to clearly see the question whether it is asking y-intercept or x-intercept. Then convert the given equation into a standard form of equation. You should remember the formula for finding y-intercept. Compare the transformed given equation with the standard equation to get the value of parameters required for computing the y-intercept.

Recently Updated Pages

Three beakers labelled as A B and C each containing 25 mL of water were taken A small amount of NaOH anhydrous CuSO4 and NaCl were added to the beakers A B and C respectively It was observed that there was an increase in the temperature of the solutions contained in beakers A and B whereas in case of beaker C the temperature of the solution falls Which one of the following statements isarecorrect i In beakers A and B exothermic process has occurred ii In beakers A and B endothermic process has occurred iii In beaker C exothermic process has occurred iv In beaker C endothermic process has occurred

The branch of science which deals with nature and natural class 10 physics CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Define absolute refractive index of a medium

Find out what do the algal bloom and redtides sign class 10 biology CBSE

Prove that the function fleft x right xn is continuous class 12 maths CBSE

Trending doubts

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

What is BLO What is the full form of BLO class 8 social science CBSE

Difference Between Plant Cell and Animal Cell

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

What is pollution? How many types of pollution? Define it